(untitled) (GYMNASIUM, 2019)
Low lumbar pain, localized or associated with a root syndrome constitutes over 50% of the cases presented in the services of physical medicine and recovery. Lumbar pain determines for temporary individuals in the current society a temporary incapacity for work. Its incidence increases with age, the physical-kinetic treatment being the most judicious treatment of lower back pain. The subjects of the research were in the number of 50 diagnosed with lower back pain, which we divided into two groups, one control and one experimental. Over the course of six months, recovery programs were applied for the patients, whom we recruited and were diagnosed with low back pain. The clinical management of persons diagnosed with low back pain is a complex one which involves the development of protocols that contain besides physical exercise and physiotherapy procedures such as laser therapy, ultrasonotherapy, the application of high and low frequency currents.